Adaptasi Kerja Jurnalis Televisi SCTV dan Indosiar Dimasa Pandemi Covid 19 - Haris, Abdul; Prayitno, Edik (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
AbstractIn doing journalistic work often faces changes that come from internal and external. The existence of Pandemic Covid 19 with various restriction rules faced the mechanism of work of television journalism to adapt to new situations. Therefore this study aims to find out the mechanism of work of SCTC and Indosiar television journalists during the 19 Pandemic Covid period. The approach in this study uses qualitative methods. The result of this study was the adaptation of SCTV-Indosiar television journalists in supporting the sustainability of their media business in the groats of Covid-19 Pandemi is to do online coverage in the Red Covid-19 zone whose resource persons cannot be found to conduct interviews with face-to-face meetings. In the online coverage process, there is an element of the UGC (User Generated Content) concept. that is, when a resource person creates his own video content in answering questions the reports given by the reporter through the WhatsApp application. This research contributes to the work strategy of television journalists in facing change.Keyword : Adaptation, Journalist, Covid 19, Television, Production